IoT-BSEM internet of things-based smart energy meter for domestic house - Abdul Razak, Nur Atiqah Husna; Ramlee, Ridza Azri; Ahmed Kamal, Ibrahim Faris; Andre, H; Khmag, Asem (2023)
This paper presents the design and development of an Internet of Things-Based Smart Energy Meter for Domestic House (IoT-BSEM). This system can monitor data from electric consumption such as the electrical appliances, to give awareness to the consumers to save energy. The system can read the data on energy consumption and manage the data in the cloud